芍藥湯 물 추출물의 항염증작용에 관한 연구 - 서윤희(Yun Hee Seo); 강옥화(Ok Hwa Kang); 권동렬(Dong Yeul Kwon); 이장석(Jang Suk Lee); 한종현(Jong Hyun Han); 이기남(Kinam Lee); 정명수(Myong Soo Chong) (동의생리병리학회지, 2011)
Jakyaktang(芍藥湯; JYT) exhibits potent anti-inflammatory activity in widely intestinal disease, but its mechanism was undisclosed. To elucidate the molecular mechanisms of JYT on pharmacological and biochemical actions in inflammation, we examined the effect of JYT on pro-inflammatory mediators in phorbol 12-myristate 13-acetate (PMA) plus A23187-induced mast cell and lipopolysaccharide (LPS)-stimulated macrophages. The investigation focused on whether JYT inhibited pro-inflammatory cytokines such as interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α) in PMA plus A23187- induced HMC-1 cells and inflammatory madiators such as nitric oxide (NO), TNF-α, IL-6, iNOS, COX-2 in LPS-stimulated RAW 264.7 cells. We found that JYT inhibited LPS-induced NO, TNF-α and IL-6 productions as well as the expressions of iNOS and COX-2. These results suggest that JYT has inhibitory effects on mast cell-mediated and macropage-mediated inflammation. Jakyaktang(芍藥湯; JYT) exhibits potent anti-inflammatory activity in widely intestinal disease, but its mechanism was undisclosed. To elucidate the molecular mechanisms of JYT on pharmacological and biochemical actions in inflammation, we examined the effect of JYT on pro-inflammatory mediators in phorbol 12-myristate 13-acetate (PMA) plus A23187-induced mast cell and lipopolysaccharide (LPS)-stimulated macrophages. The investigation focused on whether JYT inhibited pro-inflammatory cytokines such as interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-α (TNF-α) in PMA plus A23187- induced HMC-1 cells and inflammatory madiators such as nitric oxide (NO), TNF-α, IL-6, iNOS, COX-2 in LPS-stimulated RAW 264.7 cells. We found that JYT inhibited LPS-induced NO, TNF-α and IL-6 productions as well as the expressions of iNOS and COX-2. These results suggest that JYT has inhibitory effects on mast cell-mediated and macropage-mediated inflammation. KCI Citation Count: 2